Protection of Human Rights for Minors Against Acts of Sexual Abuse - Tjolleng, Arfah; Muhammad Fachri Said, (Alauddin Law Development Journal, 2024)
The state's unequivocal responsibility to safeguard children as victims of violence, particularly sexual abuse, is imperative due to their pivotal role in future development. The study method used the normative way. The research findings aim to serve as a guide for crafting policies aligning with national law, contributing positively to legal science by addressing material and formal legal aspects, as well as enhancing victim protection and recovery. The prevalence of unsettling acts of sexual harassment underscores a pressing need for vigilant attention. Child victims of sexual violence endure profound psychological impacts, ranging from mild to severe trauma, leading to a loss of self-confidence, shame, and, tragically, suicide in some cases. This study delves into child protection policies in Makassar, Indonesia, scrutinizing shortcomings in addressing sexual crimes against minors. Therefore, legal innovations for enhanced handling of such cases, ensuring justice for the victims and fostering societal balance are needed.